Pretreatment of mesenchymal stem cells with angiotensin II enhances paracrine effects, angiogenesis, gap junction formation and therapeutic efficacy for myocardial infarction. (1st June 2015) - Liu, Chao; Fan, Yue; zhou, Lu; Zhu, Hong-Yi; Song, Yi-Chen; Hu, Liang; Wang, Yu; Li, Qing-Ping
Abstract: Background: Pretreatment of mesenchymal stem cells (MSCs) with growth factors is reported to be an effective route for improving cell-based therapy of myocardial infarction (MI). Angiotensin II (Ang II) triggers vascular endothelial growth factor (VEGF) synthesis in MSCs. This study aimed to investigate the effects and mechanisms of Ang II pretreatment in enhancing the therapeutic efficacy of MSCs in MI. Methods: MSCs and endothelial cells (ECs) were isolated from Sprague-Dawley rats. After pretreated with or without 100 nM of Ang II for 24 h, the MSCs were directly injected into the border zones of the ischemic heart. Cardiac function, fibrosis, infarct size, VEGF expression, angiogenesis, and cell differentiation in the infarcted myocardium were determined after 30 days. The cell apoptosis of MSCs post hypoxia was assessed using flow cytometry. The angiogenic activity of MSCs was analyzed using tube formation assay. The gap junction protein connexin-43 (Cx43) expression was detected. Results: Compared with the MSC group, pretreatment of MSCs with Ang II resulted in better cardiac function, less cardiac fibrosis, smaller infarct size, and higher expression of VEGF and Von Willebrand Factor in ischemic myocardium, but no promotion of cardiomyocyte-like differentiation of MSCs. Ang II pretreatment enhanced the survival of MSCs and the H9c2 cells surrounding MSCs, and augmented the tube formation of ECs and MSCs. Ang II pretreatment up-regulated the Cx43 expression. Conclusions: The pretreatment of MSCs with Ang II improved the outcome of MSC-based therapy for MI via the mechanisms of enhancing the paracrine production of VEGF, angiogenesis, and gap junction formation.